Lithium iron phosphate composite material, preparation method thereof and positive plate and battery
Patent Information
- Application Number
- CN202611382017.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-16
AI Technical Summary
这些方法在一定程度上可以减小颗粒尺寸或者在一定程度上提高磷酸铁锂材料的电导率,但是其往往也带来一些问题,例如纳米化后的副反应增多或者碳包覆虽然改善电子传导但是并未优先解决颗粒内部的离子迁移瓶颈,甚至可能阻碍电解液与活性物质的接触,对材料内部电子传导性改善有限,未能真正提升磷酸铁锂快充能力
(1)本申请提供的磷酸铁锂复合材料通过“多孔内核-含锂化合物导体层-碳导电子层”的三级协同设计,系统性破解磷酸铁锂快充瓶颈。同时实现了颗粒内部(径向孔道)、颗粒表面(梯度包覆)和电极内部(垂直梯度)的三维非对称协同导电网络构建,全方位优化了传质和电荷传输过程。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a lithium iron phosphate composite material, its preparation method, a positive electrode sheet, and a battery. Background Technology
[0002] Lithium iron phosphate (LFP) has become one of the mainstream cathode materials in the power battery field, characterized by high safety, long cycle life, and low cost. However, in the application of battery materials, the low intrinsic electronic conductivity and slow lithium-ion solid-phase diffusion coefficient of LFP limit its fast-charging capability, leading to severe polarization at high-rate charging or low-temperature environments. This can easily cause lithium metal to precipitate at the negative electrode, posing a safety hazard.
[0003] Currently, common methods to improve the fast charging capability of lithium iron phosphate (LFP) materials include: nano-sizing of LFP materials, carbon coating of LFP materials, and ion doping. For example, Chinese invention patent CN107317010B discloses a coated LFP material and its preparation method, which coats the surface of LFP materials with carbon materials to obtain coated LFP. These methods can reduce particle size or improve the conductivity of LFP materials to some extent, but they often bring some problems. For example, nano-sizing increases side reactions, or although carbon coating improves electron conduction, it does not first solve the ion migration bottleneck inside the particles, and may even hinder the contact between the electrolyte and the active material, thus having limited improvement on the internal electron conduction of the material and failing to truly improve the fast charging capability of LFP.
[0004] Therefore, developing a solution that can effectively improve the fast charging capability of lithium iron phosphate has become an important research topic in battery-related materials. Summary of the Invention
[0005] In view of this, the present invention aims to at least partially solve one of the aforementioned technical problems. To this end, the present invention provides a lithium iron phosphate composite material, its preparation method, a positive electrode, and a battery. By constructing radial ion-preferential transport channels inside the lithium iron phosphate particles and building a highly efficient electron conduction network on the outside of the particles, the fast charging capability of lithium iron phosphate is significantly improved.
[0006] To solve the above-mentioned technical problems, this application is implemented as follows: The first aspect of this application provides a lithium iron phosphate composite material, comprising: A porous lithium iron phosphate secondary particle core is formed by the aggregation of primary lithium iron phosphate grains; the porous lithium iron phosphate secondary particle core includes radially arranged and interconnected channels inside. A first coating layer covers the outer surface of the porous lithium iron phosphate secondary particle core, and the first coating layer includes a lithium compound conductor layer. A second coating layer, which at least partially covers the outer surface of the first coating layer, includes a carbon conductive electronic layer.
[0007] In some optional embodiments, the porous lithium iron phosphate secondary particle core satisfies at least one of the following conditions: (1) The general chemical formula of the primary lithium iron phosphate crystal grains is Li x Fe y P z O4, where x:y:z = (1~1.1):(0.98~1):1; (2) The D50 particle size of the primary lithium iron phosphate crystals is 50nm~100nm; (3) The D50 particle size of the porous lithium iron phosphate secondary particle core is 3μm~15μm.
[0008] In some optional embodiments, the lithium iron phosphate composite material satisfies at least one of the following conditions: (1) The tap density of the lithium iron phosphate composite material is 1.20 g / cm³. 3 ~1.30g / cm 3 ; (2) The D50 particle size of the lithium iron phosphate composite material is 1.5 μm to 10 μm; (3) In the lithium iron phosphate composite material, the thickness of the first coating layer is 0.1 nm to 10 nm; (4) In the lithium iron phosphate composite material, the thickness of the second coating layer is 2 nm to 10 nm; (5) The second coating layer includes a three-dimensional carbon conductive electronics layer and a two-dimensional carbon conductive electronics layer. The three-dimensional carbon conductive electronics layer at least partially covers the outer surface of the first coating layer, and the two-dimensional carbon conductive electronics layer at least partially covers the outer surface of the three-dimensional carbon conductive electronics layer. The thickness of the three-dimensional carbon conductive electronics layer is 1 nm to 10 nm, and the thickness of the two-dimensional carbon conductive electronics layer is 0.34 nm to 3.4 nm.
[0009] The second aspect of this application provides a method for preparing lithium iron phosphate composite materials, comprising the following steps: S1. Dissolve the lithium source, iron source, phosphorus source, and first carbon source in a solvent to obtain a precursor solution; disperse the template agent in a solvent to obtain a template suspension; S2. Mix the template suspension and the precursor solution, dry and granulate to obtain lithium iron phosphate powder with template agent; S3. Remove the template agent from the lithium iron phosphate powder to obtain a porous secondary lithium iron phosphate particle core composed of primary lithium iron phosphate crystals. S4. The porous lithium iron phosphate secondary particle core, lithium source, and phosphorus source are mixed in a solution and annealed to obtain a porous lithium iron phosphate secondary particle core intermediate coated with the first coating layer. S5. The porous lithium iron phosphate secondary particle core intermediate coated by the first coating layer is dispersed in a solvent, mixed with a carbon source, and after drying, calcination and carbonization treatment, a lithium iron phosphate composite material is obtained.
[0010] In some optional embodiments, the preparation method satisfies at least one of the following conditions: (1) The drying and granulation temperature in S2 is 190℃~210℃; (2) Methods for removing template agents from lithium iron phosphate powder in S3 include pyrolysis or etching; (3) The annealing conditions described in S4 are 350℃~450℃, annealing for 1h~3h; (4) The steps of mixing with carbon source in S5 specifically include: first mixing with the second carbon source, drying and calcining to obtain a three-dimensional carbon conductive electron layer, and then mixing with the third carbon source and carbonizing to form a two-dimensional carbon conductive electron layer. (5) The drying and calcination described in S5 includes a drying process and a calcination process; the conditions of the drying process include spray drying, with an inlet temperature range of 110℃~130℃ and an outlet temperature of 90℃~100℃; the conditions of the calcination process include treatment in an inert atmosphere at 400℃~600℃ for 0.5h~2h. (6) The carbonization treatment conditions described in S5 include carbonization at an inert atmosphere of 700℃~900℃ for 1h~4h.
[0011] In some optional embodiments, the preparation method satisfies at least one of the following: (1) The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium chloride or lithium nitrate; (2) The iron source includes one or more of ferric phosphate, ferric oxide, ferrous oxalate, ferric nitrate or ferric chloride; (3) The phosphorus source includes one or more of iron phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, or lithium dihydrogen phosphate; (4) The first carbon source includes at least one of glucose, sucrose, starch, polyvinyl alcohol, polyacryl alcohol, polyethylene glycol, graphite or graphene; (5) The solvent includes at least one of deionized water, ethanol, ethylene glycol or triethanolamine; (6) The carbon source includes a second carbon source and a third carbon source; the second carbon source includes at least two of carbon black, carbon fiber tubes, graphite, graphene, multi-walled carbon nanotubes, functionalized carbon nanotubes, carbon nanospheres or graphene oxide; the third carbon source includes at least one of phenolic resin, polyacrylonitrile, glucose, sucrose, pitch or graphene. (7) The molar ratio of the lithium source, iron source, and phosphorus source is (1~1.1):(0.98~1):1; (8) The mass of the first carbon source accounts for 2% to 10% of the mass of the core of the porous lithium iron phosphate secondary particle; (9) The mass of the carbon source accounts for 3% to 10% of the mass of the core of the porous lithium iron phosphate secondary particles.
[0012] In some optional embodiments, the template agent comprises an organic template agent or an inorganic template agent; the organic template agent and the inorganic template agent satisfy at least one of the following conditions: (1) The organic template agent includes at least one of polymethyl methacrylate, polyvinylpyrrolidone, polyacrylonitrile, polystyrene, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, polypropylene, polyacrylonitrile or polyurethane; (2) The inorganic template agent includes at least one of silicon dioxide, zinc oxide, magnesium oxide, calcium carbonate, or carbon microspheres; (3) The particle size of the inorganic template agent is 50nm-100nm; (4) The mass of the organic or inorganic template agent accounts for 20% to 30% of the mass of the porous lithium iron phosphate secondary particle core.
[0013] A third aspect of this application provides a positive electrode sheet comprising the lithium iron phosphate composite material described above, or the lithium iron phosphate composite material prepared by the preparation method described above.
[0014] In some optional embodiments, the positive electrode sheet includes a positive current collector and a slurry coated on at least one surface of the positive current collector, the slurry comprising a lithium iron phosphate composite material, a binder, and a conductive agent, and satisfying at least one of the following conditions: (1) The mass ratio of the lithium iron phosphate composite material, binder, and conductive agent is (88~94):(2~8):(2~5); (2) The coating thickness of the slurry is 150μm~200μm; (3) The slurry is formed on the positive electrode current collector by directional freezing; (4) The conductive agent includes at least one of conductive graphite, acetylene black, conductive carbon black, carbon fiber, carbon nanotube or graphene. (5) The adhesive comprises at least one of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polytetrafluoroethylene or styrene-acrylate copolymer; (6) The slurry is coated after being dispersed in a solvent, wherein the solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide or N,N-dimethylacetamide.
[0015] A fourth aspect of this application provides a battery comprising the positive electrode sheet described above.
[0016] The lithium iron phosphate composite material, its preparation method, positive electrode sheet, and battery provided in this application have the following beneficial effects: (1) The lithium iron phosphate composite material provided in this application systematically solves the fast charging bottleneck of lithium iron phosphate through a three-level synergistic design of "porous core - lithium-containing compound conductor layer - carbon conductive electron layer". At the same time, it realizes the construction of a three-dimensional asymmetric synergistic conductive network in the particle interior (radial channels), particle surface (gradient coating) and electrode interior (vertical gradient), which comprehensively optimizes the mass transfer and charge transport process.
[0017] (2) The lithium iron phosphate composite material provided in this application can achieve stable fast charging at 4C and above at 25°C, and the 4C discharge capacity retention rate reaches more than 95%.
[0018] (3) The template method, coating method and directional freezing technology used in the preparation of the positive electrode of the lithium iron phosphate composite material provided in this application can all be combined with the existing industrial production process and have the potential for large-scale production.
[0019] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation
[0020] To make the technical solution and beneficial effects of this application more apparent and understandable, a detailed description is provided below by listing specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional experimental conditions. Unless otherwise specified, all reagents and raw materials used in this application are commercially available.
[0021] In the following description, numerous specific details are set forth in order to provide a more thorough understanding of this application. However, it will be apparent to those skilled in the art that this application can be practiced without one or more of these details. In other instances, to avoid confusion with this application, some technical features well-known in the art have not been described; that is, not all features of actual embodiments are described herein, nor are well-known functions and steps described in detail.
[0022] In the description of this application, it should be noted that the terms "first," "second," etc., are used for descriptive purposes only and are not intended to indicate or imply relative importance.
[0023] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0024] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0025] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0026] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0027] [Lithium iron phosphate composite material] In related technologies, porous structures are designed for lithium iron phosphate materials to create channels between lithium iron phosphate and electrolyte, thereby improving the fast charging capability of lithium iron phosphate. However, simple pores may disrupt the continuity of electron conduction.
[0028] In view of this, a first aspect of this application provides a lithium iron phosphate composite material, comprising: A porous lithium iron phosphate secondary particle core is formed by the aggregation of primary lithium iron phosphate grains; the porous lithium iron phosphate secondary particle core includes radially arranged and interconnected channels inside. A first coating layer covers the outer surface of the porous lithium iron phosphate secondary particle core, and the first coating layer includes a lithium compound conductor layer. A second coating layer, which at least partially covers the outer surface of the first coating layer, includes a carbon conductive electronic layer.
[0029] The first coating layer in this application refers to the material formed on the outer surface of the core of porous lithium iron phosphate secondary particles. This first coating layer can completely or partially cover the outer surface of the core of the porous lithium iron phosphate secondary particles, protecting the core and reducing side reactions. Since the first coating layer includes a lithium-containing compound conductor layer, it possesses excellent ionic conductivity. On the one hand, the first coating layer reduces potential side reactions in the core of the porous lithium iron phosphate secondary particles; on the other hand, it further reduces the interfacial impedance for ion extraction / intercalation on the surface of the porous lithium iron phosphate secondary particles. Similarly, the second coating layer at least partially covers the first coating layer, and can partially or completely cover the outer surface of the first coating layer. Since the second coating layer is a carbon-conducting electronic layer, and carbonaceous materials themselves possess high electronic conductivity, the second coating layer, in the presence of the first coating layer, further enables efficient collection and transport of electrons on the particle surface. The methods for determining and measuring the thickness of the first and second coating layers in this application include any conventional methods in the art. Those skilled in the art can test the thickness of the first and second coating layers using methods including, but not limited to, field emission transmission electron microscopy. Specific testing methods include: The thickness of the samples was measured using a field emission transmission electron microscope (FET). The instrument was a Thermo Scientific Talos F200X with an accelerating voltage of 200 kV, a point resolution of 0.25 nm, and a line resolution of 0.10 nm. The prepared samples were placed in the FET stage, and the high-energy electron beam passed through the samples and interacted with them, producing stereoscattering, from which the thickness data was obtained.
[0030] It should be noted that the lithium-containing compound conductor layer in the first coating layer is to provide a fast ion conductor layer for lithium ion formation. The lithium-containing compound refers to a lithium-containing salt compound; examples include lithium phosphate, lithium silicate, lithium titanate, and lithium cobalt oxide. Lithium phosphate can be used in this application, which can be obtained by reacting ammonium dihydrogen phosphate with a lithium salt (e.g., lithium nitrate or lithium hydroxide) in an ethanol-water mixed solution.
[0031] The lithium iron phosphate composite material provided in this application systematically overcomes the fast-charging bottleneck of lithium iron phosphate through a three-level synergistic design of "porous core - lithium-containing compound conductor layer - carbon conductive electron layer". The porous lithium iron phosphate secondary particle core is formed by the aggregation of primary grains, and the internal radially interconnected channels allow for deep electrolyte wetting, shortening the solid-phase diffusion path of lithium ions inside the particles from the traditional micrometer level to the nanometer level, significantly reducing concentration polarization. The lithium-containing compound in the first coating layer constructs a fast interfacial ion channel with high ionic conductivity, while also acting as a physical barrier to inhibit electrolyte decomposition and reduce interfacial charge transfer impedance. The second coating layer enables efficient collection and transport of electrons on the particle surface. Through the spatial layered design of the composite material provided in this application, the lithium ion transport path and the electron transport path are decoupled within the material, allowing them to operate independently and efficiently in their respective optimized channels, completely breaking the inherent contradiction of "mutual constraint between ion and electron transport" in traditional modification methods. The lithium iron phosphate composite material provided in this application achieves a capacity retention of 95.8% at 4C rate and 99.2% after 100 cycles, while maintaining a tap density of 1.30 g / cm³. 3 It combines high rate performance with high energy density, providing a brand-new solution for fast-charging lithium batteries.
[0032] Porous lithium iron phosphate secondary particle core In some optional embodiments, the general chemical formula of the primary lithium iron phosphate crystals is Li. x Fe y P z O4, where x:y:z = (1~1.1):(0.98~1):1; as an example, x:y:z can be 1:0.98:1, 1.05:1:1, 1.1:0.98:1, 1:1:1, etc.
[0033] In some optional embodiments, the D50 particle size of the primary lithium iron phosphate crystals is 50nm~100nm; as an example, the D50 particle size of the primary lithium iron phosphate crystals can be 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, etc.
[0034] In some optional embodiments, the D50 particle size of the porous lithium iron phosphate secondary particle core is 3μm-15μm; as an example, the D50 particle size of the porous lithium iron phosphate secondary particle core can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc.
[0035] In this application, the "porous lithium iron phosphate secondary particle core" refers to the lithium-ion storage host that constitutes the basic framework of the lithium iron phosphate composite material. The porous lithium iron phosphate secondary particle core is a micron-sized aggregate with a secondary structure formed by the stacking and agglomeration of multiple nano-sized primary lithium iron phosphate grains. The secondary particle core contains a rich network of pores formed by gaps between primary grains, grain boundaries, or cavities left after the removal of the pore-forming template agent. In the structural hierarchy of this application, the porous lithium iron phosphate secondary particle core is located in the central region of the particle system, with its outer surface serving as a substrate to support the subsequent coating layer. In this application, the first coating layer covering the outer surface of the porous lithium iron phosphate secondary particle core can be formed only on the outermost geometric surface of the porous lithium iron phosphate secondary particle core, or it can penetrate into the inner wall of the open pores within a certain depth range of the core surface, forming an interface bond with a mechanical interlocking effect. As an example, the first coating layer can be formed on the outermost geometric surface of the porous lithium iron phosphate secondary particle core.
[0036] The porous lithium iron phosphate secondary particle core provided in this application has a porous structure composed of nanoscale primary grains. The electrolyte can penetrate deep into the interior of the secondary particles through the pore network, significantly shortening the diffusion path of lithium ions in the solid phase (i.e., the transport distance from the particle surface to the internal lithium intercalation site is reduced from the traditional micrometer-level radial distance to the radius distance of a nanometer-level primary grain). This structural feature significantly reduces concentration polarization during lithium ion extraction / intercalation. Furthermore, the porous outer surface of the porous lithium iron phosphate secondary particle core has a larger specific surface area and higher number of surface chemically active sites compared to a dense solid sphere surface. This is beneficial for the uniformity and adhesion of the subsequent first coating layer on the surface of the porous lithium iron phosphate secondary particle core, preventing the first coating layer from peeling off.
[0037] In this application, the primary lithium iron phosphate grains can be characterized by SEM / TEM electron microscopy; the particle size parameters of the porous lithium iron phosphate secondary particle core can be determined by laser particle size analyzer, and specific reference can be made to GB / T 19077-2016 "Particle size analysis by laser diffraction".
[0038] In some optional embodiments, the tap density of the lithium iron phosphate composite material is 1.20 g / cm³. 3 ~1.30g / cm 3 As an example, the tap density of lithium iron phosphate composite materials can be 1.20 g / cm³. 3 1.23g / cm 3 1.25g / cm 3 1.27g / cm 3 1.28g / cm 3 1.30g / cm 3Optionally, the tap density of the lithium iron phosphate composite material is 1.23 g / cm³. 3 ~1.30g / cm 3 The lithium iron phosphate composite material provided in this application maintains a suitable powder compaction density while ensuring abundant internal channels. This facilitates achieving higher compaction density during electrode rolling and prevents over-compression leading to particle breakage, thereby improving electrode compaction density and battery volumetric energy density. The lithium iron phosphate composite material provided in this application maintains a suitable powder compaction density of 1.23 g / cm³ while ensuring abundant internal channels. 3 ~1.30g / cm 3 A suitable tap density within the specified range avoids both the problem of insufficient volumetric energy density due to excessively low tap density and the risk of deteriorating electrochemical performance due to excessively high tap density.
[0039] The tap density described in this application can be determined by loading a certain amount of composite material powder into a container and compacting the powder using a mechanical vibration device until its volume no longer decreases. The tap density is the mass of the powder at this point divided by the compacted volume. Alternatively, refer to GB / T 5162-2021 "Determination of Tap Density of Metal Powders" for the fixed mass method (measuring cylinder method). Weigh 20.00 g of sample, vibrate at a frequency of 100–120 times / min, with an amplitude of 3 mm, vibrate for 10 min, read the compacted volume, and calculate the tap density using ρ=m / V.
[0040] In some optional embodiments, the D50 particle size of the lithium iron phosphate composite material is 1.5 μm to 10 μm; as an example, the D50 particle size of the lithium iron phosphate composite material can be 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, etc., or of course, any value within the above range.
[0041] In some optional implementations, the thickness of the first coating layer is 0.1 nm to 10 nm; as an example, the thickness of the first coating layer can be 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 3 nm, 5.5 nm, 6 nm, 7.5 nm, 9 nm, etc., or any value within the above range.
[0042] In some optional embodiments, the thickness of the second coating layer is 2nm to 10nm; as an example, the thickness of the second coating layer can be 2nm, 5nm, 7nm, 9nm, 10nm, etc., or any value within the above range.
[0043] Further research in this application has revealed that when the second coating layer optionally meets the following settings, the fast charging capability and rate performance of lithium iron phosphate composite materials used in batteries can be further improved.
[0044] Optionally, the second coating layer includes a three-dimensional carbon conductive electron layer and a two-dimensional carbon conductive electron layer. The purpose of this dual-layer carbon conductive electron layer architecture is to solve the problem of limited rate performance caused by the low intrinsic electronic conductivity of lithium iron phosphate materials. By constructing differentiated conductive pathways of "bulk collection" and "inter-surface transport", the electronic conduction efficiency is optimized at both the microscopic single-particle scale and the macroscopic electrode scale.
[0045] Optionally, the three-dimensional carbon conductive electronic layer at least partially covers the outer surface of the first coating layer.
[0046] In this application, the "three-dimensional carbon conductive electronics layer" refers to an amorphous carbon layer or a partially graphitized carbon layer with a three-dimensional spatial network structure formed on the outer surface of the first coating layer. This three-dimensional carbon conductive electronics layer can completely or partially cover the outer surface of the first coating layer and provide an elastic buffer space for the volume change of the porous lithium iron phosphate secondary particle core during charging and discharging.
[0047] Lithium iron phosphate (LFP) is an electronic insulator. Its first coating layer is a lithium-containing compound conductor layer with excellent ionic conductivity but limited electronic conductivity. A three-dimensional carbon conductive electron layer tightly coats the outside of the first coating layer. Because the carbonaceous material used in the three-dimensional carbon conductive electron layer has high electronic conductivity, it can construct continuous electron transport channels on the surface of the porous LFP secondary particle core. This efficiently collects electrons generated during lithium-ion intercalation / deintercalation from the surface of the first coating layer and converges them into the three-dimensional conductive network framework. This process achieves low-impedance, full-coverage electron collection from the surface of the porous LFP secondary particle core, integrating discrete electron generation points into a unified electron output terminal.
[0048] Further optionally, the thickness of the three-dimensional carbon conductive electronic layer is 1nm to 10nm; as an example, the thickness of the three-dimensional carbon conductive electronic layer can be 1nm, 3nm, 5nm, 7nm, 8nm, 10nm, etc., or of course any value within the above range.
[0049] Optionally, the two-dimensional carbon conductive electronic layer at least partially covers the outer surface of the three-dimensional carbon conductive electronic layer.
[0050] In this application, the "two-dimensional carbon conductive electronic layer" refers to a conductive carbon layer formed on the outer surface of a three-dimensional carbon conductive electronic layer, exhibiting a high degree of graphitization and a two-dimensional sheet structure. The two-dimensional carbon conductive electronic layer can completely or partially cover the outer surface of the three-dimensional carbon conductive electronic layer. Microscopically, this carbon layer presents as a sheet-like carbon structure with significant two-dimensional extension characteristics. Its carbon atoms are arranged with high orientation and order, and the carbon layer planes are preferentially oriented along the tangential direction of the three-dimensional carbon conductive electronic layer surface, forming a continuous shell structure with high electronic conductivity.
[0051] Because the two-dimensional carbon conductive electron layer has a highly conductive plane, electrons can be rapidly conducted laterally through the plane of the two-dimensional carbon conductive electron layer, crossing the gaps between particles from the three-dimensional conductive network of one particle to enter the conductive network of adjacent particles. This process transforms the electron transport between particles from the high-resistance mode of traditional point contact to the low-resistance mode of two-dimensional surface conduction, solving the bottleneck problem of electron transport between "points".
[0052] Further optionally, the thickness of the two-dimensional carbon conductive electronic layer is 0.34 nm to 3.4 nm. As an example, the thickness of the two-dimensional carbon conductive electronic layer can be 0.34 nm to 1 nm; in other embodiments, the thickness of the two-dimensional carbon conductive electronic layer can be 1 nm to 2 nm; in other embodiments, the thickness of the two-dimensional carbon conductive electronic layer can be 2 nm to 3.4 nm.
[0053] Specifically, in some embodiments, the thickness of the two-dimensional carbon conductive electronic layer can be 0.5nm, 0.8nm, 1.2nm, 1.8nm, 2.5nm, 3nm, or 3.4nm, etc.
[0054] It should be noted that the thickness values described above are merely examples of some embodiments of this application and are not intended to limit the scope of this application. Those skilled in the art can adjust the fabrication process within the above range to obtain the required thickness of the two-dimensional carbon conductive electronic layer according to actual product performance requirements.
[0055] The thickness of the lithium iron phosphate composite material involved in this application can be tested using a field emission transmission electron microscope.
[0056] [Preparation method of lithium iron phosphate composite material] The second aspect of this application provides a method for preparing lithium iron phosphate composite materials, comprising the following steps: S1. Dissolve the lithium source, iron source, phosphorus source, and first carbon source in a solvent to obtain a precursor solution; disperse the template agent in a solvent to obtain a template suspension; S2. Mix the template suspension and the precursor solution, dry and granulate to obtain lithium iron phosphate powder with template agent; S3. Remove the template agent from the lithium iron phosphate powder to obtain a porous secondary lithium iron phosphate particle core composed of primary lithium iron phosphate crystals. S4. The porous lithium iron phosphate secondary particle core, lithium source, and phosphorus source are mixed in a solution and annealed to obtain a porous lithium iron phosphate secondary particle core intermediate coated with the first coating layer. S5. The porous lithium iron phosphate secondary particle core intermediate coated by the first coating layer is dispersed in a solvent, mixed with a carbon source, and after drying, calcination and carbonization treatment, a lithium iron phosphate composite material is obtained.
[0057] The preparation method provided in this application is simple and easy to implement, can be combined with existing industrial production processes, and has the potential for large-scale production.
[0058] It should be understood that all the features and advantages described above regarding "lithium iron phosphate composite materials" also apply to this "preparation method of lithium iron phosphate composite materials", and will not be repeated here.
[0059] In some optional embodiments, the drying and granulation temperature in S2 is 190℃~210℃; as an example, the temperature can be 190℃, 200℃, 210℃, 220℃, etc., as long as it does not depart from the core idea of the present invention, and the specific parameter adjustments should not limit the purpose of the present invention. The drying and granulation method is spray drying; the spraying method can be ultrasonic spraying, centrifugal spraying, cyclone spraying, pressurized spraying, vacuum spraying, and charge repulsion spraying, etc., which are commonly used in the art, and are not limited to the methods listed above, and do not limit the purpose of the present invention.
[0060] In some alternative implementations, the method for removing the template agent from the lithium iron phosphate powder in S3 includes pyrolysis or etching.
[0061] Alternatively, the method for removing the template agent from the lithium iron phosphate powder in S3 can be pyrolysis.
[0062] Furthermore, the template agent is decomposed and released through pyrolysis, forming a porous structure.
[0063] Alternatively, the method for removing the template agent from the lithium iron phosphate powder in S3 can be etching. The specific etching method and etchant are not specifically limited, only that the template agent can be selectively removed without damaging the lithium iron phosphate matrix.
[0064] In some optional embodiments, the annealing conditions described in S4 are 350℃~450℃ for 1h~3h; as an example, the annealing conditions described in S4 can be annealing at 350℃ for 3h, 400℃ for 2h, 430℃ for 1.5h, or 450℃ for 1h, etc. As long as it does not depart from the core idea of the present invention, the specific parameters adjusted within the scope of the disclosure of this application should not constitute a limitation on the purpose of the present invention.
[0065] In some optional embodiments, the step of mixing with the carbon source in S5 specifically includes: first mixing with a second carbon source, drying and calcining to obtain a three-dimensional carbon conductive electronics layer, and then mixing with a third carbon source and carbonizing to form a two-dimensional carbon conductive electronics layer.
[0066] In some optional embodiments, the drying and calcination in S5 includes a drying process and a calcination process; the conditions of the drying process include spray drying with an inlet temperature range of 110°C to 130°C and an outlet temperature of 90°C to 100°C; the conditions of the calcination process include treatment in an inert atmosphere at 400°C to 600°C for 0.5h to 2h.
[0067] In some optional embodiments, the carbonization treatment conditions described in S5 include carbonization at 700°C to 900°C in an inert atmosphere for 1 to 4 hours; as an example, the carbonization treatment conditions may be carbonization at 800°C in an inert atmosphere for 2 hours or carbonization at 900°C in an inert atmosphere for 1 hour, etc. As long as it does not depart from the core idea of the present invention, the specific parameters in S5 adjusted within the scope of the disclosure of this application should not constitute a limitation on the purpose of the present invention.
[0068] The second and third carbon sources in this application may be the same or different. Preferably, the second and third carbon sources in this application are different.
[0069] Further optionally, the second carbon source and the third carbon source are different. The second carbon source includes at least two of carbon black, carbon fiber tubes, graphite, graphene, multi-walled carbon nanotubes, functionalized carbon nanotubes, carbon nanospheres, or graphene oxide; the third carbon source includes at least one of phenolic resin, polyacrylonitrile, glucose, sucrose, pitch, or graphene.
[0070] Furthermore, the second carbon source includes graphene oxide and functionalized carbon nanotubes; further still, the functionalized carbon nanotubes include, but are not limited to, carboxylated single-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes, hydroxylated carbon nanotubes, aminated carbon nanotubes, sulfonated carbon nanotubes, etc.; optionally, the second carbon source includes graphene oxide and carboxylated multi-walled carbon nanotubes; as an example, the mass ratio of graphene oxide to carboxylated multi-walled carbon nanotubes can be 1:1, 2:1, or 3:1, etc., and as long as it does not depart from the core idea of the present invention, the specific adjustment of the mass ratio should not constitute a limitation on the purpose of the present invention. The third carbon source includes pitch.
[0071] This application constructs a "porous core—fast ion conductor intermediate layer—three-dimensional carbon conductive framework—two-dimensional carbon dense coating layer," achieving "asymmetric" and "gradient" functional design at the particle, interface, and electrode levels. This enables synergistic optimization of ion and electron transport, significantly improving the fast-charging performance and cycle stability of lithium iron phosphate materials. Specifically, the three-dimensional carbon conductive layer is composed of graphene oxide and carboxylated carbon nanotubes, which form a long-range conductive network with interpenetrating "surface-line" structures through π-π stacking and hydrogen bonding self-assembly, significantly reducing the intra- and inter-particle electron transport impedance of lithium iron phosphate particles; the two-dimensional carbon conductive layer is constructed by pitch pyrolysis using sp... 2 A hybrid dense carbon film coating fills micropores and establishes lateral transport channels with low contact resistance between particles, while simultaneously isolating the electrolyte from contact with the lithium iron phosphate active material and suppressing interfacial side reactions. The radially interconnected channels in the porous lithium iron phosphate secondary particle core shorten the lithium-ion solid-phase diffusion path, and the fast-ion conductor interlayer promotes interfacial lithium-ion transport. This multi-level synergy effectively improves the high-rate capacity retention and cycle stability of the lithium iron phosphate composite material.
[0072] In some optional embodiments, the mass of the first carbon source accounts for 2% to 10% of the mass of the porous lithium iron phosphate secondary particle core; as an example, the mass of the first carbon source accounting for 2%, 3%, 5%, 8%, 10% of the mass of the porous lithium iron phosphate secondary particle core may be 3% to 10% of the mass of the porous lithium iron phosphate secondary particle core; as an example, the mass of the carbon source accounting for 3%, 5%, 7%, 9%, 10% of the mass of the porous lithium iron phosphate secondary particle core may be 3%, 5%, 7%, 9%, 10% of the mass of the porous lithium iron phosphate secondary particle core may be 10%.
[0073] In some optional embodiments, the lithium source in S1 includes, but is not limited to, one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium chloride, or lithium nitrate; the iron source includes, but is not limited to, one or more of iron phosphate, ferric oxide, ferrous oxalate, iron nitrate, or iron chloride; the phosphorus source includes, but is not limited to, one or more of iron phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, or lithium dihydrogen phosphate; the first carbon source includes, but is not limited to, at least one of glucose, sucrose, starch, polyvinyl alcohol, polyacryl alcohol, polyethylene glycol, graphite, or graphene; and the solvent includes, but is not limited to, at least one of deionized water, ethanol, ethylene glycol, or triethanolamine.
[0074] Further optionally, the molar ratio of the lithium source, iron source, and phosphorus source is (1~1.1):(0.98~1):1; as an example, the molar ratio of the lithium source, iron source, and phosphorus source can be 1:1:1, 1:0.98:1, 1:0.99:1, 1.05:1:1, 1.05:0.98:1, 1.1:1:1, 1.1:0.98:1, etc.
[0075] In some alternative embodiments, the template agent includes an organic template agent or an inorganic template agent.
[0076] In some optional embodiments, the template agent may be an organic template agent. More optionally, the organic template agent includes at least one selected from polymethyl methacrylate, polyvinylpyrrolidone, polyacrylonitrile, polystyrene, polyethylene oxide-propylene oxide-ethylene oxide triblock copolymer, polypropylene, polyacrylonitrile, or polyurethane. As an example: When using an organic template agent, the method for removing the organic template agent from the lithium iron phosphate powder in S3 includes: pyrolyzing the lithium iron phosphate powder containing the template agent under a non-oxidizing atmosphere to thermally decompose and remove the organic template agent; more specifically, the method for removing the organic template agent from the lithium iron phosphate powder in S3 includes: calcining the lithium iron phosphate powder containing the organic template agent obtained in S2 in a tube furnace, introducing a mixture of inert gas and hydrogen (hydrogen gas fraction of 5%~10%), and the calcination program is to heat to 300℃~350℃ at a rate of 1℃ / min~5℃ / min and hold for 2h~4h; during this stage, the organic template agent is thermally decomposed, vaporized, and carried away by the carrier gas, leaving interconnected channels inside the particles, and then the temperature is increased to 650~700℃ at a rate of 1℃ / min~10℃ / min and held for 10~12h, during which lithium iron phosphate crystals grow, forming a porous lithium iron phosphate secondary particle core composed of primary nanocrystals.
[0077] In some optional embodiments, the template agent may be an inorganic template agent. Further optionally, the inorganic template agent includes at least one of silicon dioxide, zinc oxide, magnesium oxide, calcium carbonate, or carbon microspheres. As an example: when using an inorganic template agent, in S3 the inorganic template agent in the lithium iron phosphate powder is removed by selective etching. Specifically, an etchant capable of selectively dissolving the inorganic template agent without significantly eroding the lithium iron phosphate matrix is used; this allows the inorganic template agent to be selectively removed, forming a porous structure without damaging the lithium iron phosphate matrix.
[0078] As an optional implementation, the etchant includes, but is not limited to, aqueous solutions of sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, ammonium bifluoride, hydrofluoric acid, and buffered oxide etchant (BOE). For example, the etchant may be an aqueous solution of hydrofluoric acid, wherein the mass concentration of the hydrofluoric acid solution is 5 wt% to 10 wt%.
[0079] In this step, hydrofluoric acid aqueous solution acts as a selective etching agent, specifically used to remove inorganic template agents without damaging the lithium iron phosphate host material. Inorganic template agents such as silica, zinc oxide, magnesium oxide, calcium carbonate, or carbon microspheres are chemically inert to most acids (such as hydrochloric acid, sulfuric acid, and nitric acid) at room temperature, but they can undergo a specific reaction with hydrofluoric acid. Taking silica as an example of an inorganic template agent, the reaction mechanism lies in F… - The ions nucleophilically attack the Si-O bond, taking advantage of the fact that the Si-F bond energy is much higher than the Si-O bond energy, causing the Si-O bond to break and generating soluble fluorosilicic acid or volatile silicon tetrafluoride. The specific reaction equations are shown in Equations I and II: SiO2 + 4HF → SiF4↑ + 2H2O (Formula I) or SiO2 + 6HF → H2SiF6 + 2H2O (excess hydrofluoric acid) Formula II As an example, the method for removing the inorganic template agent from the lithium iron phosphate powder in S3 includes: etching removal using a hydrofluoric acid aqueous solution, preparing a 5-10 wt% hydrofluoric acid aqueous solution, adding the lithium iron phosphate powder with the inorganic template agent in S2 to the hydrofluoric acid aqueous solution, and stirring at room temperature for 4-6 hours; after the reaction is completed, the reaction mixture is poured into a large amount of saturated lime water or dilute ammonia water for preliminary neutralization, consuming most of the free hydrofluoric acid, and then filtered, washed and dried to obtain a porous lithium iron phosphate secondary particle core composed of primary lithium iron phosphate crystals.
[0080] Further optionally, the particle size of the inorganic template agent is 50nm-100nm; as an example, the particle size of the inorganic template agent can be 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, etc.
[0081] As an optional implementation, the organic or inorganic template agent accounts for 20% to 30% of the mass of the porous lithium iron phosphate secondary particle core.
[0082] A radially arranged through-hole structure formed by the aggregation of primary nanocrystals was constructed inside secondary lithium iron phosphate particles using a volatile template method. This structure allows the electrolyte to rapidly wet into the particle interior along the pores, and the lithium ion solid-phase diffusion distance is compressed to the primary grain scale (50nm~100nm), significantly reducing the solid-phase diffusion resistance.
[0083] [Positive electrode tablets] A third aspect of this application provides a positive electrode sheet prepared from the lithium iron phosphate composite material described in any of the above embodiments, or prepared from the lithium iron phosphate composite material prepared by the preparation method described in any of the above embodiments.
[0084] The positive electrode includes the lithium iron phosphate composite material provided in this application, and therefore, the positive electrode also has excellent electrochemical performance.
[0085] In some alternative embodiments, the positive electrode sheet includes a positive current collector and a slurry coated on at least one surface of the positive current collector; the slurry includes a lithium iron phosphate composite material, a binder, and a conductive agent.
[0086] In some optional embodiments, the mass ratio of the lithium iron phosphate composite material, binder, and conductive agent is (88~94):(2~8):(2~5); in this application, the mass content of the lithium iron phosphate composite material is 88%~94%; the mass content of the binder is 2%~8%; and the mass content of the conductive agent is 2%~5%.
[0087] In some optional embodiments, the coating thickness of the slurry is 150μm to 200μm; as an example, the coating thickness can be 150μm, 160μm, 180μm, 200μm, etc.
[0088] In some alternative embodiments, the slurry is formed on the positive current collector by directional freezing.
[0089] In some alternative embodiments, the conductive agent includes, but is not limited to, at least one of conductive graphite, acetylene black, conductive carbon black, carbon fiber, carbon nanotubes, or graphene. As an example, the conductive agent may be acetylene black, the Super P series (optional models such as Super P, Super S), Ketjen black, etc.
[0090] In some alternative embodiments, the adhesive includes, but is not limited to, at least one of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polytetrafluoroethylene, or styrene-acrylate copolymer.
[0091] In some alternative embodiments, the slurry is coated after being dispersed in a solvent, the solvent including at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, or N,N-dimethylacetamide.
[0092] The final positive electrode sheet has a dense electronic conductive network on the side near the positive current collector and more ion transport channels and higher porosity on the side near the separator, which facilitates electrolyte wetting and rapid ion migration.
[0093] It should be noted that the types of conductive agents, binders, and solvents mentioned above are merely examples and are not limited to the substances listed above. Any conductive agents, binders, and solvents that can be used in the field of batteries are applicable and do not limit the purpose of this invention. Other similar conductive agents, binders, and solvents can also be used in this invention.
[0094] In some optional embodiments, this application also provides a method for preparing a positive electrode sheet, comprising the following steps: (1) The lithium iron phosphate composite material, binder, and conductive agent are mixed in a solvent at a mass ratio of 90~95:(1~4):4 to form a positive electrode slurry; (2) Coat the positive electrode slurry onto the current collector, with the thickness controlled at 150-200 μm; (3) Place the coated electrode in step (2) horizontally above liquid nitrogen for directional freezing; (4) Transfer the frozen electrode sheet from step (3) to a freeze dryer and dry for 24-48 hours to obtain the positive electrode sheet.
[0095] The directional freezing temperature is -10 to -20°C, and the time is 20 to 35 minutes. Directional freezing is used to process the coated electrode. Directional freezing causes the solvent in the slurry to crystallize and sublimate, forcing the conductive agent and binder to redistribute in the direction perpendicular to the current collector, forming a vertical gradient conductive structure with a "dense at the bottom and sparse at the top" inside the electrode.
[0096] In addition, as an improvement to the positive electrode sheet of this application, other functional additives known in the art for improving electrode performance may be added to the positive electrode sheet, such as one or more of plasticizers, dispersants, pore-forming agents, stabilizers, film-forming additives, wetting agents, pH adjusters, etc., which will not be elaborated here.
[0097] [Battery] A fourth aspect of this application provides a battery comprising the positive electrode sheet described above.
[0098] In this embodiment, the battery also includes a negative electrode, a separator, and an electrolyte; and the specific type of battery is not limited. For example, the battery can be any one of a cylindrical lithium battery, a pouch lithium battery, or an aluminum-cased lithium battery.
[0099] The battery includes the lithium iron phosphate composite material provided in the embodiments of this application. Therefore, the battery also has excellent electrochemical performance, such as high rate capacity retention and excellent cycle stability.
[0100] Since the battery provided in this embodiment of the invention adopts all the technical solutions in the above embodiments, it has at least all the beneficial effects brought about by the technical solutions in the above embodiments, and will not be described in detail here.
[0101] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0102] Example 1 (1) Preparation of lithium iron phosphate composite materials S1: Weigh lithium hydroxide, ferrous sulfate and ammonium dihydrogen phosphate according to the molar ratio of lithium source, iron source and phosphorus source of 1.05:1:1, dissolve them in deionized water, stir until completely dissolved, add sucrose (accounting for 5% of the theoretical mass of lithium iron phosphate) and stir until completely dissolved to obtain the precursor solution. Polymethyl methacrylate (25% of the theoretical mass of lithium iron phosphate, model: EPRUI-CPA-300, purchased from Shanghai Epurui Biotechnology Co., Ltd.) was dispersed in deionized water to obtain a template suspension.
[0103] S2: The precursor solution and template suspension in S1 are thoroughly mixed and granulated by spray drying at a temperature of 200℃ to obtain lithium iron phosphate powder with template agent.
[0104] S3: The lithium iron phosphate powder containing the template agent from S2 is calcined in a tube furnace, and a mixture of argon and hydrogen is introduced, with hydrogen accounting for 5% of the volume of the mixture; the temperature is increased to 350℃ at a rate of 2℃ / min and held for 2 hours. Then the temperature is increased to 650℃ at a rate of 5℃ / min and held for 10 hours to obtain a porous secondary lithium iron phosphate particle core composed of primary lithium iron phosphate grains.
[0105] S4: The porous lithium iron phosphate secondary particle cores formed by the aggregation of primary lithium iron phosphate crystals in S3 are dispersed in an ethanol-water mixed solution (volume ratio of ethanol to water is 1:1) composed of ammonium dihydrogen phosphate and lithium hydroxide (molar ratio of ammonium dihydrogen phosphate to lithium hydroxide is 1:3). The mixture is stirred continuously at 60°C for 4 hours. After washing and filtration, the mixture is annealed at 400°C for 2 hours to form a porous lithium iron phosphate secondary particle core intermediate coated with a first coating layer (Li3PO4). The Li3PO4 coating amount is 3wt% of the mass of lithium iron phosphate.
[0106] S5: Preparation of the second coating layer: The porous lithium iron phosphate secondary particle core intermediate coated by the first coating layer (Li3PO4) is redispersed in deionized water and mixed with the second carbon source (graphene oxide dispersion and carboxylated multi-walled carbon nanotube dispersion, the mass of the second carbon source accounts for 2wt% of the mass of lithium iron phosphate, and the mass ratio of graphene oxide dispersion to carboxylated multi-walled carbon nanotube dispersion is 3:1). The mixture is stirred and ultrasonicated, dried, and heat-treated at 500℃ in an inert atmosphere for 1 h to obtain a three-dimensional carbon conductive electronics layer. Then, it is mixed with the third carbon source (asphalt solution dissolved in N-methylpyrrolidone, the mass of the third carbon source accounts for 2wt% of the mass of lithium iron phosphate). After evaporating the N-methylpyrrolidone, it is carbonized at 800℃ in an inert atmosphere for 2 h to form a two-dimensional carbon conductive electronics layer, thus obtaining the lithium iron phosphate composite material.
[0107] The general chemical formula of primary lithium iron phosphate crystals is Li. 1.05 Fe1P1O4, with a D50 particle size of 80 nm; The D50 particle size of the porous lithium iron phosphate secondary particle core is 5 μm; The thickness of the first coating layer is 5 nm; The thickness of the three-dimensional carbon conductive electronic layer is 8 nm, and the thickness of the two-dimensional carbon conductive electronic layer is 3 nm. The D50 particle size of the lithium iron phosphate composite material is 5 μm.
[0108] Graphene oxide dispersion was purchased from Fangda Carbon New Material Technology Co., Ltd.; carboxylated multi-walled carbon nanotube dispersion, model FT7000, was purchased from Jiangsu Tiannai Technology Co., Ltd.
[0109] (2) Preparation of positive electrode sheet M1: The lithium iron phosphate composite material prepared in (1), binder (polyvinylidene fluoride, model Solef5130, from Solvay Group), and conductive agent (Ketjen black and SP mixed in a mass ratio of 1:1) are mixed in a solvent (N-methylpyrrolidone) at a mass ratio of 92:4:4 to form a positive electrode slurry; M2: The positive electrode slurry is coated on the positive electrode current collector (aluminum foil), and the thickness on both sides is controlled at 180μm (excluding the thickness of the current collector). M3: Immediately place the coated electrode from M2 horizontally above liquid nitrogen for directional freezing at a temperature of -20°C for 30 minutes.
[0110] M4: The frozen electrode sheet in M3 is quickly transferred to a freeze dryer and dried for 24 hours to obtain the positive electrode sheet.
[0111] (3) Battery assembly The positive electrode obtained in (2) above is assembled with the negative electrode, electrolyte and separator to obtain a battery.
[0112] The negative electrode active material (graphite), conductive agent (conductive carbon), binder (styrene-butadiene rubber) and dispersant (carboxymethyl cellulose) are mixed in a mass ratio of 96.6:1:1.5:0.9, and water is added and stirred to prepare a negative electrode slurry. The negative electrode slurry is uniformly coated on the negative electrode current collector copper foil, and after drying, cold pressing and other processes, a negative electrode sheet is obtained.
[0113] The electrolyte was a solution of 1 mol / L LiPF6 in EC+DEC+DMC in a volume ratio of 1:1:1.
[0114] The positive and negative electrode sheets and the separator are wound and hot-pressed, and the core is put into an aluminum-plastic film. The core is then vacuum dried, injected with liquid, packaged, left to stand, and subjected to formation and capacity testing to obtain a lithium-ion battery.
[0115] Example 2 The preparation method of the lithium iron phosphate composite material provided in this embodiment is the same as that in Embodiment 1. The difference from Embodiment 1 is that the M3 step of preparing the positive electrode sheet is placed in an oven for drying and is not subjected to directional freezing to obtain the positive electrode sheet.
[0116] The general chemical formula of primary lithium iron phosphate crystals is Li. 1.05 Fe1P1O4, with a D50 particle size of 80 nm; The D50 particle size of the porous lithium iron phosphate secondary particle core is 5 μm; The thickness of the first coating layer is 5 nm; The thickness of the three-dimensional carbon conductive electronic layer is 8 nm, and the thickness of the two-dimensional carbon conductive electronic layer is 3 nm. The D50 particle size of the lithium iron phosphate composite material is 5 μm.
[0117] Example 3 The specific implementation method of the lithium iron phosphate composite material provided in this embodiment is the same as that in embodiment 1. The difference from embodiment 1 is that it does not contain a two-dimensional carbon conductive electronic layer. That is, after obtaining a three-dimensional carbon conductive electronic layer in S5, the preparation of the lithium iron phosphate composite material can be completed.
[0118] The general chemical formula of primary lithium iron phosphate crystals is Li. 1.05Fe1P1O4, with a D50 particle size of 80 nm; The D50 particle size of the porous lithium iron phosphate secondary particle core is 5 μm; The thickness of the first coating layer is 5 nm; The thickness of the three-dimensional carbon conductive electronic layer is 8 nm; The D50 particle size of the lithium iron phosphate composite material is 5 μm.
[0119] Example 4 The specific implementation method is the same as in Example 1, except that the preparation of the lithium iron phosphate composite material only proceeds to step S3 of Example 1. Steps S4 and S5 are replaced with traditional sucrose pyrolysis carbon coating. The specific steps are as follows: Sucrose is dissolved in water, and the porous lithium iron phosphate secondary particle cores with aggregated primary lithium iron phosphate crystals obtained in S3 are added and stirred to form a uniform suspension. The amount of sucrose added is 10% of the mass of the porous lithium iron phosphate secondary particle cores with aggregated primary lithium iron phosphate crystals. The mixture is dried, and the dried powder is placed in a tube furnace and heat-treated under inert nitrogen gas protection at a pyrolysis temperature of 700℃ for 20 hours at a heating rate of 5℃ / min. After pyrolysis, the mixture is cooled to room temperature to obtain carbon-coated lithium iron phosphate.
[0120] Example 5 The specific implementation method is the same as in Example 1, except that steps S1 to S3 are different from Example 1, and inorganic template agent silicon dioxide is used. Specifically, it includes: S1`: Weigh lithium hydroxide, ferrous sulfate and ammonium dihydrogen phosphate according to the molar ratio of lithium source, iron source and phosphorus source of 1.05:1:1, dissolve them in deionized water, stir until completely dissolved, add sucrose (accounting for 5% of the theoretical mass of lithium iron phosphate) and stir until completely dissolved to obtain the precursor solution. A template suspension was prepared by dispersing silica nanospheres (accounting for 20% of the theoretical mass of lithium iron phosphate) in deionized water and then treating them with ultrasound. S2': The template suspension in S1' is thoroughly mixed with the precursor solution, and granulation is carried out by spray drying at a temperature of 200℃; lithium iron phosphate powder with template agent is obtained. S3': Prepare a 5wt% hydrofluoric acid aqueous solution, add the lithium iron phosphate powder with SiO2 template obtained in S2 to the hydrofluoric acid aqueous solution, and stir at room temperature for 4 hours; after the reaction is completed, pour the reaction mixture into a large amount of saturated lime water for neutralization, and then filter, wash and dry to obtain a porous lithium iron phosphate secondary particle core composed of primary lithium iron phosphate crystals.
[0121] The subsequent steps S4 to S5 are the same as those in Example 1.
[0122] The general chemical formula of primary lithium iron phosphate crystals is Li.1.05 Fe1P1O4, with a D50 particle size of 80 nm; The D50 particle size of the porous lithium iron phosphate secondary particle core is 7 μm; The thickness of the first coating layer is 5 nm; The thickness of the second coating layer is 11 nm; The D50 particle size of the lithium iron phosphate composite material is 7 μm.
[0123] Comparative Example 1 In this example, ordinary carbon-coated lithium iron phosphate material (model A8-4E, purchased from Hubei Wanrun) was used directly without any special design. The positive electrode sheet adopted the conventional oven drying process as in Example 2.
[0124] Comparative Example 2 The specific implementation method in this example is the same as in Example 1. The difference is that the lithium iron phosphate composite material does not have a first coating layer, and the preparation process S3 is directly carried out in step S5.
[0125] The general chemical formula of primary lithium iron phosphate crystals is Li. 1.05 Fe1P1O4, D50 particle size is 100nm; The D50 particle size of the porous lithium iron phosphate secondary particle core is 6μm; The thickness of the three-dimensional carbon conductive electronic layer is 8 nm, and the thickness of the two-dimensional carbon conductive electronic layer is 3 nm. The D50 particle size of the lithium iron phosphate composite material is 6 μm.
[0126] Comparative Example 3 The specific implementation method in this example is the same as in Example 1. The difference from Example 1 is that there is no three-dimensional carbon conductive electronic layer. After S4, it is directly mixed with the third carbon source (asphalt solution dissolved in N-methylpyrrolidone, the mass of the third carbon source accounts for 2wt% of the mass of lithium iron phosphate). After evaporating N-methylpyrrolidone, it is carbonized for 2 hours in an inert atmosphere at 800°C to form a two-dimensional carbon conductive electronic layer, thus obtaining the lithium iron phosphate composite material.
[0127] The general chemical formula of primary lithium iron phosphate crystals is Li. 1.05 Fe1P1O4, with a D50 particle size of 80 nm; The D50 particle size of the porous lithium iron phosphate secondary particle core is 5 μm; The thickness of the first coating layer is 5 nm; The thickness of the two-dimensional carbon conductive electronic layer is 3 nm; The D50 particle size of the lithium iron phosphate composite material is 5 μm.
[0128] Comparative Example 4 The specific implementation method in this example is the same as in Example 1, except that a template agent is not used. The specific steps include: S1``: Weigh lithium hydroxide, ferrous sulfate and ammonium dihydrogen phosphate according to the molar ratio of lithium source, iron source and phosphorus source of 1.05:1:1, dissolve them in deionized water, stir until completely dissolved, add sucrose (accounting for 5% of the theoretical mass of lithium iron phosphate), stir until completely dissolved, and obtain the precursor solution.
[0129] S2``: The precursor solution in S1 is granulated by spray drying at a temperature of 200℃ to obtain lithium iron phosphate powder.
[0130] S3``: The lithium iron phosphate powder in S2 is dispersed in an ethanol-water mixed solution (volume ratio of ethanol to water is 1:1) composed of ammonium dihydrogen phosphate and lithium hydroxide (molar ratio of ammonium dihydrogen phosphate to lithium hydroxide is 1:3). The mixture is stirred continuously at 60°C for 4 hours. After washing and filtration, the mixture is annealed at 400°C for 2 hours to form a lithium iron phosphate powder intermediate coated with the first coating layer (Li3PO4). The amount of Li3PO4 coating is 3wt% of the mass of lithium iron phosphate.
[0131] S4``: The lithium iron phosphate powder intermediate coated with the first coating layer (Li3PO4) is redispersed in deionized water and mixed with the second carbon source (graphene oxide dispersion and carboxylated multi-walled carbon nanotube dispersion, the second carbon source accounts for 2wt% of the mass of lithium iron phosphate, and the mass ratio of graphene oxide dispersion to carboxylated multi-walled carbon nanotube dispersion is 3:1). The mixture is stirred and ultrasonicated, dried, and heat-treated at 500°C in an inert atmosphere for 1 hour to obtain a three-dimensional carbon conductive electronics layer. Then, it is mixed with the third carbon source (asphalt solution dissolved in N-methylpyrrolidone, the third carbon source accounts for 2wt% of the mass of lithium iron phosphate). After evaporating N-methylpyrrolidone, it is carbonized at 800°C in an inert atmosphere for 2 hours to form a two-dimensional carbon conductive electronics layer, thus obtaining the lithium iron phosphate composite material.
[0132] The general chemical formula of primary lithium iron phosphate crystals is Li. 1.05 Fe1P1O4, with a D50 particle size of 80 nm; The D50 particle size of the porous lithium iron phosphate secondary particle core is 3μm; The thickness of the first coating layer is 5 nm; The thickness of the three-dimensional carbon conductive electronic layer is 8 nm, and the thickness of the two-dimensional carbon conductive electronic layer is 3 nm. The D50 particle size of the lithium iron phosphate composite material is 3 μm.
[0133] Performance testing The lithium iron phosphate composite materials and batteries obtained in the above embodiments and comparative examples were subjected to performance tests, specifically including: (1) Tap density of lithium iron phosphate composite material: Test reference standard: GB / T 5162-2021, test results are shown in Table 1.
[0134] (2) Battery performance test, the test results are shown in Table 2.
[0135] 2.1: First Coulomb efficiency test: The battery was placed at 25℃±2℃ and charged at a constant current and constant voltage of 1C until the voltage reached 3.65V and the cutoff current was 0.05C. The initial charge capacity was recorded. The battery was then left to rest for 15 minutes, and finally discharged at a constant current of 1C until the voltage reached 2.0V. The initial discharge capacity was recorded. The formula for calculating the initial discharge efficiency of the battery is: Initial coulombic efficiency = (Initial discharge capacity / Initial charge capacity) × 100%.
[0136] 2.2: 4C Discharge Capacity Retention Rate Test: Under an ambient temperature of 25℃±2℃, the battery is fully charged using the standard charging method and left to stand for 5 minutes; then discharged at 1C constant current to 2.0V, left to stand for 30 minutes, charged at 1C constant current and constant voltage to 3.65V, left to stand for 30 minutes, and discharged at 1C constant current to 2.0V to obtain the 1C discharge capacity; left to stand for 30 minutes, charged at 1C constant current and constant voltage to 3.65V, left to stand for 30 minutes, and discharged at 4C constant current to 2.0V to obtain the 4C discharge capacity. The 4C discharge capacity / 1C discharge capacity * 100% is the 4C discharge capacity retention rate.
[0137] 2.3: Cycle capacity retention test: The battery was placed at 25℃±2℃, discharged at 1C constant current to 2.5V, left to stand for 15min, charged at 1C constant current and constant voltage to 3.65V, cut-off current was 0.05C, left to stand for 15min, discharged at 1C constant current to 2.5V, and the above steps were repeated 100 times. Cycle capacity retention rate = (discharge capacity of the 100th cycle / discharge capacity of the 1st cycle) × 100%.
[0138] Table 1 Test results of lithium iron phosphate composite materials
[0139] Table 2 Battery Test Results
[0140] The data in Table 1 shows that the lithium iron phosphate composite material provided in this application maintains a suitable tap density while ensuring abundant internal channels. This avoids the problem of insufficient volumetric energy density due to excessively low tap density (see Comparative Example 1) and also prevents the risk of deterioration in electrochemical performance due to excessively high tap density (see Comparative Example 4). This demonstrates that this application achieves synergistic optimization of tap density and electrochemical performance by constructing radial ion-preferred transport channels inside the lithium iron phosphate particles and building an efficient electron conduction network on the outside of the particles. This lays the foundation for achieving initial improvements in coulombic efficiency, fast-charging performance, and cycle capacity retention when used in batteries.
[0141] By comparing the initial discharge capacity and initial coulombic efficiency data of the examples and comparative examples, it can be seen that: Comparative Example 3, which does not have a three-dimensional carbon conductive electron layer, has an initial discharge specific capacity that is significantly lower than that of Example 1. The initial discharge specific capacity of the solid lithium iron phosphate in Comparative Example 4 is also significantly lower than that of Example 1. This proves that the improvement of the lithium iron phosphate composite material provided in this application has played a substantial role in internal ion diffusion. It shows that after solving the ion diffusion problem, internal electron conduction is also a very important technical challenge for lithium iron phosphate materials, which has been overcome in this application.
[0142] Example 1 shows an initial discharge capacity of 158.37 mAh / g. The lithium iron phosphate composite material provided in this application ensures rapid lithium ion insertion / extraction; the three-dimensional carbon network and vertical electrode channels ensure high-speed electron transport; the dense two-dimensional carbon conductive electron layer and Li3PO4 layer effectively suppress side reactions, significantly improving the battery capacity and initial efficiency.
[0143] Comparing the 4C discharge capacity retention data of the examples and comparative examples, it can be seen that the 4C discharge capacity retention of Example 1 can reach over 95%, while the 4C discharge capacity retention of Comparative Example 4 is only 74%. This shows that the construction of internal porous ion channels plays a decisive role in high-rate performance. The lithium iron phosphate composite material provided in this application fundamentally improves the fast-charging capability of traditional lithium iron phosphate.
[0144] Comparing Example 1 and Comparative Example 3, it can be seen that the three-dimensional carbon conductive electron layer network can guide electrons deep into the particles, thereby improving rate performance. Comparing Example 1 and Example 2, it can be seen that the vertical channels constructed by directional freeze-drying technology can significantly reduce concentration polarization at high rates.
[0145] By comparing the capacity retention data of the embodiments and the comparative examples after 100 cycles at 1C, it can be seen that the cycle retention rate of Example 1 reaches 99.2%, while that of Comparative Example 2 is only 93.7%. It can be seen that the Li3PO4 coating layer has a significant effect on interface stability. This application avoids continuous electrolyte decomposition and transition metal dissolution by setting the Li3PO4 conductor layer, thus avoiding the loss of active lithium iron phosphate and active materials.
[0146] In summary, the lithium iron phosphate composite material with a unique asymmetric gradient conductive network structure in this invention solves the two core problems of "transmission bottleneck" at high rates and "interface degradation" under long cycles.
[0147] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0148] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0149] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0150] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium iron phosphate composite material, characterized in that, include: A porous lithium iron phosphate secondary particle core is formed by the aggregation of primary lithium iron phosphate grains; the porous lithium iron phosphate secondary particle core includes radially arranged and interconnected channels inside. A first coating layer covers the outer surface of the porous lithium iron phosphate secondary particle core, and the first coating layer includes a lithium compound conductor layer. A second coating layer, which at least partially covers the outer surface of the first coating layer, includes a carbon conductive electronic layer.
2. The lithium iron phosphate composite material according to claim 1, characterized in that, The porous lithium iron phosphate secondary particle core satisfies at least one of the following conditions: (1) The general chemical formula of the primary lithium iron phosphate crystal grains is Li x Fe y P z O4, where x:y:z = (1~1.1):(0.98~1):1; (2) The D50 particle size of the primary lithium iron phosphate crystals is 50nm~100nm; (3) The D50 particle size of the porous lithium iron phosphate secondary particle core is 3μm to 15μm.
3. The lithium iron phosphate composite material according to claim 1 or 2, characterized in that, The lithium iron phosphate composite material satisfies at least one of the following conditions: (1) The tap density of the lithium iron phosphate composite material is 1.20 g / cm³. 3 ~1.30g / cm 3 ; (2) The D50 particle size of the lithium iron phosphate composite material is 1.5 μm to 10 μm; (3) In the lithium iron phosphate composite material, the thickness of the first coating layer is 0.1 nm to 10 nm; (4) In the lithium iron phosphate composite material, the thickness of the second coating layer is 2 nm to 10 nm; (5) The second coating layer includes a three-dimensional carbon conductive electronics layer and a two-dimensional carbon conductive electronics layer. The three-dimensional carbon conductive electronics layer at least partially covers the outer surface of the first coating layer, and the two-dimensional carbon conductive electronics layer at least partially covers the outer surface of the three-dimensional carbon conductive electronics layer. The thickness of the three-dimensional carbon conductive electronics layer is 1 nm to 10 nm, and the thickness of the two-dimensional carbon conductive electronics layer is 0.34 nm to 3.4 nm.
4. A method for preparing a lithium iron phosphate composite material, characterized in that, Includes the following steps: S1. Dissolve the lithium source, iron source, phosphorus source, and first carbon source in a solvent to obtain a precursor solution; disperse the template agent in a solvent to obtain a template suspension; S2. Mix the template suspension and the precursor solution, dry and granulate to obtain lithium iron phosphate powder with template agent; S3. Remove the template agent from the lithium iron phosphate powder to obtain a porous secondary lithium iron phosphate particle core composed of primary lithium iron phosphate crystals. S4. The porous lithium iron phosphate secondary particle core, lithium source, and phosphorus source are mixed in a solution and annealed to obtain a porous lithium iron phosphate secondary particle core intermediate coated with the first coating layer. S5. The porous lithium iron phosphate secondary particle core intermediate coated by the first coating layer is dispersed in a solvent, mixed with a carbon source, and after drying, calcination and carbonization treatment, a lithium iron phosphate composite material is obtained.
5. The method for preparing the lithium iron phosphate composite material according to claim 4, characterized in that, The preparation method satisfies at least one of the following conditions: (1) The drying and granulation temperature in S2 is 190℃~210℃; (2) Methods for removing template agents from lithium iron phosphate powder in S3 include pyrolysis or etching; (3) The annealing conditions described in S4 are 350℃~450℃, annealing for 1h~3h; (4) The steps of mixing with carbon source in S5 specifically include: first mixing with the second carbon source, drying and calcining to obtain a three-dimensional carbon conductive electron layer, and then mixing with the third carbon source and carbonizing to form a two-dimensional carbon conductive electron layer. (5) The drying and calcination described in S5 includes a drying process and a calcination process; the conditions of the drying process include spray drying, with an inlet temperature range of 110℃~130℃ and an outlet temperature of 90℃~100℃; the conditions of the calcination process include treatment in an inert atmosphere at 400℃~600℃ for 0.5h~2h. (6) The carbonization treatment conditions described in S5 include carbonization at an inert atmosphere of 700℃~900℃ for 1h~4h.
6. The method for preparing the lithium iron phosphate composite material according to claim 4, characterized in that, The preparation method satisfies at least one of the following: (1) The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium chloride or lithium nitrate; (2) The iron source includes one or more of ferric phosphate, ferric oxide, ferrous oxalate, ferric nitrate or ferric chloride; (3) The phosphorus source includes one or more of iron phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, or lithium dihydrogen phosphate; (4) The first carbon source includes at least one of glucose, sucrose, starch, polyvinyl alcohol, polyacryl alcohol, polyethylene glycol, graphite or graphene; (5) The solvent includes at least one of deionized water, ethanol, ethylene glycol or triethanolamine; (6) The carbon source includes a second carbon source and a third carbon source; the second carbon source includes at least two of carbon black, carbon fiber tubes, graphite, graphene, multi-walled carbon nanotubes, functionalized carbon nanotubes, carbon nanospheres or graphene oxide; the third carbon source includes at least one of phenolic resin, polyacrylonitrile, glucose, sucrose, pitch or graphene. (7) The molar ratio of the lithium source, iron source, and phosphorus source is (1~1.1):(0.98~1):1; (8) The mass of the first carbon source accounts for 2% to 10% of the mass of the core of the porous lithium iron phosphate secondary particle; (9) The mass of the carbon source accounts for 3% to 10% of the mass of the core of the porous lithium iron phosphate secondary particles.
7. The method for preparing the lithium iron phosphate composite material according to claim 4, characterized in that, The template agent includes an organic template agent or an inorganic template agent; the organic template agent and the inorganic template agent satisfy at least one of the following conditions: (1) The organic template agent includes at least one of polymethyl methacrylate, polyvinylpyrrolidone, polyacrylonitrile, polystyrene, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, polypropylene, polyacrylonitrile or polyurethane; (2) The inorganic template agent includes at least one of silicon dioxide, zinc oxide, magnesium oxide, calcium carbonate, or carbon microspheres; (3) The particle size of the inorganic template agent is 50nm-100nm; (4) The mass of the organic or inorganic template agent accounts for 20% to 30% of the mass of the porous lithium iron phosphate secondary particle core.
8. A positive electrode plate, characterized in that, The lithium iron phosphate composite material according to any one of claims 1 to 3, or the lithium iron phosphate composite material prepared by the preparation method according to any one of claims 4 to 7.
9. The positive electrode sheet according to claim 8, characterized in that, The positive electrode sheet includes a positive current collector and a slurry coated on at least one surface of the positive current collector. The slurry includes a lithium iron phosphate composite material, a binder, and a conductive agent, and satisfies at least one of the following conditions: (1) The mass ratio of the lithium iron phosphate composite material, binder, and conductive agent is (88~94):(2~8):(2~5); (2) The coating thickness of the slurry is 150μm~200μm; (3) The slurry is formed on the positive electrode current collector by directional freezing; (4) The conductive agent includes at least one of conductive graphite, acetylene black, conductive carbon black, carbon fiber, carbon nanotube or graphene. (5) The adhesive comprises at least one of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polytetrafluoroethylene or styrene-acrylate copolymer; (6) The slurry is coated after being dispersed in a solvent, wherein the solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide or N,N-dimethylacetamide.
10. A battery, characterized in that, Includes the positive electrode sheet as described in claim 8 or 9.
Citation Information
Patent Citations
A coated lithium iron phosphate material and its preparation method
CN107317010B